METODE DAN CORAK TAFSÎR GHARÎB AL-MUWATTÂ’ KARYA ‘ABD AL-MÂLIK BIN HABÎB - Naf'atu Fina, Lien Iffah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2018)
This article discusses a review book of al-Muwattâ’ titled Tafsîr Gharîb al-Muwattâ’ by Abû Marwân ‘Abd al-Mâlik bin Habîb, an Andalusian Mâliki scholar who lived in the range 174-238 H. The discussion includes the author figure, the status of the book and the contents, systematics as well as the method. The reception of this book will also be discussed at the end of the writing. This book explains gharîb or abstruse words in al-Muwattâ’ both in a language and a fiqh explanation. Abû Marwân,  has placed the scope of gharîb al-hadîth broader than usual. Unlike the other essay of Abû Marwân, al-Wadihah, Tafsîr Gharîb al-Muwattâ’ did not receive a positive response, because the contribution of this book is not too significant, other than because of carelessness in narration. Abû Marwân not only saw this gharîb from the linguistic aspect, but also from the fiqh aspect, so that it was not always the words described in gharîb language, but words or sentences that did need further explanation fiqh, even though the word is actually not gharîb linguistically. The advantage of this book lies in its method of being able to present a book that is practical, easy to understand and applicable, not long-winded.Keyword: Tafsîr, Gharîb, al-Muwattâ’, ‘Abd al-Mâlik bin Habîb